2016
DOI: 10.3233/jad-160860
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder and Frontotemporal Dementia: An Intriguing Association

Abstract: Bipolar disorder (BD) could represent a prodromal state of frontotemporal dementia (FTD). Two patients affected by lifelong BD with a progressive decline of cognitive functions, behavioral, and neurological signs, reached the early diagnosis of FTD before the age of 60. They were diagnosed as affected by primary progressive aphasia and FTD with parkinsonism, respectively. A diagnosis of FTD should therefore be taken into account, in case of unexpected cognitive and behavioral decline in patients with a long hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 55 publications
1
30
0
2
Order By: Relevance
“…There appears to be an increased risk of bvFTD and nfvPPA before age 60 in those with BD, with documented cases of patients with a lifelong diagnosis of BD evolving to these frontotemporal degenerations. 20 22 In these patients, there may be a shared genetic predisposition to both BD and bvFTD, as previously noted from C9orf72 mutations. 23 Investigators have reported C9orf72 mutations in patients with BD preceding bvFTD, with possible genetic expansion from BD to bvFTD.…”
Section: Discussionsupporting
confidence: 52%
“…There appears to be an increased risk of bvFTD and nfvPPA before age 60 in those with BD, with documented cases of patients with a lifelong diagnosis of BD evolving to these frontotemporal degenerations. 20 22 In these patients, there may be a shared genetic predisposition to both BD and bvFTD, as previously noted from C9orf72 mutations. 23 Investigators have reported C9orf72 mutations in patients with BD preceding bvFTD, with possible genetic expansion from BD to bvFTD.…”
Section: Discussionsupporting
confidence: 52%
“…We have focused our study on comparing EO-OABD with bvFTD due to the intriguing associations with this specific type of dementia. Several ways of approaching the question of a relationship between BD and FTD were synthesized by Papazacharias et al (23), including: "(1) sharing pre-disposing factors, mainly genetics, (2) causal relationship in which BD patients are at greater risk for developing FTD, (3) reverse relationship in which FTD presents with a bipolar-like syndrome, (4) sporadic co-occurrence of BD and FTD, (5) late-onset BD preceding the diagnosis of FTD, or (6) specific dementia syndrome arising as a result of bipolarity but that does not seem to correspond to the criteria of the main types of dementia, including FTD." Possibly all these cases can be found in clinical practice.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…The link between OABD and FTLD, particularly with the behavioral variant of frontotemporal dementia (bvFTD), is complex and heterogeneous. On the one hand, clinical reports have described that early-onset OABD patients may develop progressive cognitive impairment, particularly in executive functions (EF), together with behavioral changes and predominant atrophy in frontotemporal regions, constituting cases in which a differential diagnosis regarding frontotemporal dementia (FTD) is challenging (19,20,(22)(23)(24)(25). However, the link between bvFTD and BD involves also lateonset OABD, with patients who initiate mood and behavioral alterations at ≥50 years old and that may exhibit similar symptoms to those observed in bvFTD (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of BD evolving into FTD have been reported . However, clinical diagnostic markers for FTD, particularly the behavioural variant (bv‐FTD), include early clinical and behavioural symptoms that were lacking at onset and have been absent throughout his illness.…”
Section: Discussionmentioning
confidence: 99%